Diagnostic and therapeutic difficulties of tick-borne encephalitis – a two case reports - Przetacznik, Dominika; Leksa, Natalia; Aebisher, David; Galiniak, Sabina; Bartosz, Seweryn; Leksa, Dawid; Bartusik-Aebisher, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. The paper presents epidemiology, routes of infection, forms of the disease, diagnostic and treatment methods, and prophylaxis of tick-borne encephalitis. Aim. In this paper, we present two descriptions of the cases of tick-borne encephalitis. Description of the cases. Case 1. A 60-year-old man with fever up to 39 degrees for 3 days, multi-site headache and other body aches, as well as an earstuck feeling. The day before hospitalization, there was a feeling of numbness on the right side of the face from eye level to the chin and speech distortion. Case 2. A 60-year-old patient with headaches and an increase in temperature to 39 degrees for 3 days, who, approximately, three weeks earlier was ticked by a tick in the lower parts of the back. Conclusion. It is also important for doctors to take a broader view and to make society aware of that Lyme disease is not associated only with Lyme disease. Further work is also needed towards effective treatments for Tick-borne encephalitis (TBE).
Keywords: diagnostic; tick borne encephalitis; treatments